Paroxysmal supraventricular tachycardia as first manifestation of right atrial hemangioma during endovascular treatment of intracranial arteriovenous fistulas - Spanò, Francesca (Oncotarget, 2015)
We report the description of a cardiac mass occupying almost the entire right atrium in a young man who developed paroxysmal supraventricular tachycardia during endovascular treatment of intracranial arteriovenous fistulas. The mass was detected at echocardiographic examination, its tissue characteristics were defined with cardiac magnetic resonance and it was successfully surgically removed. The histopathological findings were consistent with a mixed type cavernous-capillary hemangioma of the heart. The intriguing co-existence of cardiac hemangioma and cerebral arteriovenous fistulas, to the best of our knowledge, has not been previously reported in English Literature.